2017
DOI: 10.1038/srep42557
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Invertebrate Larval Settlement; Different Bacteria, Different Mechanisms?

Abstract: Recruitment via settlement of pelagic larvae is critical for the persistence of benthic marine populations. For many benthic invertebrates, larval settlement occurs in response to surface microbial films. Larvae of the serpulid polychaete Hydroides elegans can be induced to settle by single bacterial species. Until now, only Pseudoalteromonas luteoviolacea had been subjected to detailed genetic and mechanistic studies. To determine if the complex structures, termed tailocins, derived from phage-tail gene assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 67 publications
4
107
0
1
Order By: Relevance
“…P1-9, because of its moderately anti-fungal activity and the presence of several genes assigned to NRPS within the genome. 13 Strain P1-9 was cultivated on a 50 L scale using modified SWCL medium (stirring, 30 ° C). Culture supernatant was extracted using XAD16 resin and the resulting crude extract was fractionated using an established C18-SPE purification protocol.…”
Section: Isolation Of Bioactive Secondary Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…P1-9, because of its moderately anti-fungal activity and the presence of several genes assigned to NRPS within the genome. 13 Strain P1-9 was cultivated on a 50 L scale using modified SWCL medium (stirring, 30 ° C). Culture supernatant was extracted using XAD16 resin and the resulting crude extract was fractionated using an established C18-SPE purification protocol.…”
Section: Isolation Of Bioactive Secondary Metabolitesmentioning
confidence: 99%
“…In another study, Hadfield and co-workers reported that amongst other not yet identified chemical signals, 13 phage tail-like bacteriocins derived from Pseudoalteromonas luteoviolacea induce larval settlement in the marine invertebrate Hydroides elegans . 14,15 As a third example, Clardy and co-workers elucidated the absolute structure of a rosette-inducing factor (RIF-1, 7 ) produced by the prey bacterium Algoriphagus machipongonensis of the choanoflagellate Salpingoeca rosetta .…”
Section: Introductionmentioning
confidence: 99%
“…). Metamorphosis of H. elegans is also triggered by taxonomically distant strains of Cellulophaga lytica , Bacillus aquimaris and Staphylococcus warneri , suggesting that there might be conserved mechanisms that induce settlement and metamorphosis (Freckelton et al ., ). This is also the case for other marine organisms such as macroalgal zoospores (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…The diversity and taxonomic resolution of cobble communities using metabarcoding illustrate the potential of WRMS to detect DNA profiles of specific species and explore community interactions between member species at a small scale. Many marine invertebrates experience dispersive larval stages in which they settle on surfaces in response to environmental cues (Freckelton, Nedved, & Hadfield, ). These surfaces play a pivotal role in larval habitat selection and can influence postsettlement survival (Harrington, Fabricius, De'Ath, & Negri, ).…”
Section: Discussionmentioning
confidence: 99%